An Integrative Approach to Al-Ghazali and Carl Jung in the Psychology of Learning within Islamic Religious Education - Syawaldi, Syawaldi; Charles, Charles (El-Rusyd, 2025)
This study aims to formulate an integrative learning psychology model that unifies Al-Ghazali’s methodology of Tazkiyatun Nafs with Carl Jung’s Individuation process as a transformative framework for Islamic Religious Education. The research departs from a critique of contemporary Islamic Religious Education, which tends to be predominantly cognitive-normative and therefore fails to cultivate inner transformation and holistic character development in learners. Through a comparative-theoretical literature study, this research analyzes the structural and functional correspondences between Islamic psychological concepts Nafs, Qalb, Ruh, and Tazkiyah and Jungian concepts such as the Shadow, Ego, Collective Unconscious, and the Self. The findings indicate a strong functional equivalence, particularly between Nafs Ammarah and the Shadow, as well as between Qalb and the Self/Depth Unconscious. This synthesis produces the “Tazkiyah-Individuation Learning Psychology Model,” which consists of three main stages: Takhalli (purification from psychic inferiority/Shadow), Tahalli (cultivation of akhlaq al-karimah and strengthening of the Ego–Self Axis), and Tajalli (spiritual actualization analogous to Self-Realization). The model offers a procedural framework for Islamic Religious Education curricula to integrate moral development, mental well-being, and spirituality into the learning process. This research concludes that integrating the two theories can bridge methodological gaps in the psychology of religion and provide a robust theoretical foundation for developing holistic character education. However, since this study remains theoretical, further research is needed to empirically examine the model’s effectiveness within Islamic Religious Education and psycho-spiritual counseling contexts.